Research Trends on the Use of Chemistry Comics Based on Project-Based Learning to Improve Science Process Skills - Rizka Sofia Irawan; Aris Doyan; Samsul Sahidi; Ridha Zulfatun Nafisah; Muhammad Isro’; Hidayatullah Hidayatullah; Nisa Hidayatullah; Riska Dia Sapitri; Ryya Aulia Assirri (Current Educational Review, 2026)
Chemistry learning requires students not only to understand abstract concepts but also to engage in scientific activities that form the foundation of science process skills; therefore, instructional innovations that support concept visualization and foster inquiry are essential. In this context, the present study aims to analyze research trends on the use of Project-Based Learning (PjBL) chemistry comic media to enhance students’ science process skills during the period 2016–2025. This study employed a descriptive–analytical method using a bibliometric approach by examining 1,000 Google Scholar–indexed documents with the assistance of Publish or Perish and Dimensions AI to identify publication patterns, dominant keywords, and the most influential journal sources. The findings indicate a significant increase in publications since 2022, with both print and digital comics emerging as effective media for visualizing chemical concepts and supporting scientific work within PjBL. These findings align with Bruner’s constructivism and Paivio’s Dual Coding Theory, which emphasize the importance of visual representation and authentic learning experiences. The study concludes that integrating chemistry comics with PjBL has strong theoretical and empirical legitimacy as an approach capable of strengthening students’ science process skills. Practically, the results suggest the need for more systematic implementation of comics and PjBL in science curricula to support creative, contextual, and scientifically literate learning